2020
DOI: 10.4218/etrij.2018-0632
|View full text |Cite
|
Sign up to set email alerts
|

Energy‐efficient data transmission technique for wireless sensor networks based on DSC and virtual MIMO

Abstract: In a wireless sensor network (WSN), the data transmission technique based on the cooperative multiple‐input multiple‐output (CMIMO) scheme reduces the energy consumption of sensor nodes quite effectively by utilizing the space‐time block coding scheme. However, in networks with high node density, the scheme is ineffective due to the high degree of correlated data. Therefore, to enhance the energy efficiency in high node density WSNs, we implemented the distributed source coding (DSC) with the virtual multiple‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…CMIMO scheme reduces the energy consumption of sensor nodes quite effectively by using the space-time block coding scheme. However, in [ 19 ] it is shown that in networks with high node density, the scheme is ineffective due to the high degree of correlated data. Therefore, to enhance the energy efficiency in these cases, the authors propose to use the distributed source coding (DSC) with the virtual MIMO data transmission technique.…”
Section: Energy Conservationmentioning
confidence: 99%
“…CMIMO scheme reduces the energy consumption of sensor nodes quite effectively by using the space-time block coding scheme. However, in [ 19 ] it is shown that in networks with high node density, the scheme is ineffective due to the high degree of correlated data. Therefore, to enhance the energy efficiency in these cases, the authors propose to use the distributed source coding (DSC) with the virtual MIMO data transmission technique.…”
Section: Energy Conservationmentioning
confidence: 99%
“…The proposed scheme was able to deliver the local publication to the core domain and solves the issue in remote publication routing into the edge domain, allowing the objects to be routed aptly to the subscribers. Zhang and Dong [19] have examined few issues in routing such as the delay in transmission and proposed a bypassing void routing protocol. The whole theory was dependent upon the virtual coordinates to prevent the void problem V. CONCLUSION In this paper, we have discussed the overview on routing protocls (its ,features, advantages, disadvantages), Routing protocol, Wireless network and security with the concept of data transfer, in the paper, in which we get to know about what is different protocols its survey how important it is and how it has been used and the issues that should kept in mind for the betterment of a reliable and comfortable result.…”
Section: IVmentioning
confidence: 99%
“…It is not energy efficient for long distance communication and also provides low data rate. The V-MIMO technique is used to increase the data rate and reduce energy consumption for long distance communication in WSN [10]. But, WSN covers a large area.…”
Section: Problem Description and Proposed Workmentioning
confidence: 99%
“…Now, in Fig. 2b, 2c, the total energy for transmitting a bit using V-SIMO and V-MISO communication in a single hop is given by (9) and (10) (3)…”
Section: Energy Consumption Analysis Of Multihop Mimo Techniquementioning
confidence: 99%
See 1 more Smart Citation